Preparing Parents for Discharge from the Neonatal Unit, the Transition, and Care of Their Preterm Children at Home - Osorio Galeano, Sandra Patricia; Salazar Maya, Ángela María (Investigación y Educación en Enfermería, 2023)
Preparing parents to care for their preterm children is one of the principal challenges faced by nursing professionals within the neonatal care contexts. This process seeks for parents to acquire the skills to safely provide the differential care required by children at home given their prematurity condition. The preparation for discharge is complex and multidimensional, involving aspects that have to do with the knowledge, skills for caring, security, and trust to transit and take care of the children at home. This process is conducted in the neonatal unit gradually, in function of the clinical evolution of the children and the adaptation of the parents to the situation, considering their individual, family, social, and cultural characteristics. This article describes the principal aspects related with the preparation for discharge and the transition to the home, contents of the education that must be provided to the parents or principal caregivers, and the recommendations for the professional practice regarding these types of educational processes, aimed at making visible and facilitating the nursing role and follow up of results in the health and wellbeing of the preterm children, their parents, and families.